Nano‐silicon fertiliser increases the yield and quality of cherry radish - Xinxin Xu; Yaozu Guo; Yi Hao; Zeyu Cai; Yini Cao; Wanzhen Fang; Bangyin Zhao; Christy L. Haynes; Jason C. White; Chuanxin Ma (Modern Agriculture)
Abstract Although silicon‐based nanomaterials (Si‐based NMs) can promote crop yield and alleviate biotic and abiotic stress, the underlying performance mechanisms are unknown. In the present study, the effect of the root application of Si‐based NMs on the physiological responses of cherry radish (Raphanus sativus L.) was evaluated in a life cycle experiment. Root exposure to 0.1% (w/w) Si‐based NMs significantly increased total fresh weight, total chlorophyll and carotenoids by 36.0%, 14.2% and 18.7%, respectively, relative to untreated controls. The nutritional content of the edible tissue was significantly enhanced, with an increase of 23.7% in reducing sugar, 24.8% in total sugar, and 232.7% in proteins; in addition, a number of nutritional elements (Cu, Mn, Fe, Zn, K, Ca, and P) were increased. Si‐based NMs exposure positively altered the phytohormone network and decreased abscisic acid content, both of which promoted radish fresh weight. LC‐MS‐based metabolomic analysis shows that Si‐based NMs increased the contents of most carbohydrates (e.g., α‐D‐glucose, acetylgalactosamine, lactose, fructose, etc.) and amino acids (e.g., asparagine, glutamic acid, glutamine, valine, arginine, etc.), subsequently improving overall nutritional values. Overall, nanoscale Si‐based agrochemicals have significant potential as a novel strategy for the biofortification of vegetable crops in sustainable nano‐enabled agriculture.